2013
DOI: 10.1103/physreva.87.013823
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the transition between Autler-Townes splitting and electromagnetically-induced-transparency models

Abstract: Two phenomena can affect the transmission of a weak signal field through an absorbing medium in the presence of a strong additional field: electromagnetically induced transparency (EIT) and Autler-Townes splitting (ATS). Being able to discriminate between the two is important for various applications. Here we present an experimental investigation into a method that allows for such a disambiguation as proposed in [Phys. Rev. Lett. 107, 163604 (2011)]. We apply the proposed test based on Akaike's information cri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“…They have successfully applied this test to an experiment with a one-dimensional (1D) superconducting transmission line coupled to a flux qubit, concluding that the reported data 16 do not support the claim of EIT. In a recent study, Giner et al 49 demonstrated the suitability of the AIC criterion to evaluate EIT and ATS in experiments with cold caesium atoms. Oishi et al 50 suggested that the transient response of a system can be used to discern EIT from ATS.…”
mentioning
confidence: 99%
“…They have successfully applied this test to an experiment with a one-dimensional (1D) superconducting transmission line coupled to a flux qubit, concluding that the reported data 16 do not support the claim of EIT. In a recent study, Giner et al 49 demonstrated the suitability of the AIC criterion to evaluate EIT and ATS in experiments with cold caesium atoms. Oishi et al 50 suggested that the transient response of a system can be used to discern EIT from ATS.…”
mentioning
confidence: 99%
“…Our investigation adds a fresh applications-based perspective to the ongoing discussion centered on phenomenon-based comparisons between EIT and ATS [4,5,[7][8][9][10][11]. Further, it clarifies any potential confusion that may arise between the two perceivably similar EIT and ATS memory protocols, which is important because by understanding the underlying mechanisms of these memories, a proper approach to optimization can be taken: one that yields the best results for a given set of technical and design limitations.…”
Section: Discussionmentioning
confidence: 95%
“…This common feature has been at the centre of a longstanding confusion as to whether an observed transparency is due to EIT or ATS, and as such, the distinction between the two is an active topic of research in the quantum optics community. Recently, it has been shown theoretically [4][5][6] as well as experimentally [7][8][9][10][11] that it is possible to objectively distinguish the regime where EIT dominates (EIT regime) from the one where ATS dominates (ATS regime).…”
Section: Introductionmentioning
confidence: 99%
“…The two phenomena coexist and the contribution from the EIT prevails over that originating from the A-T effect at low coupling Rabi frequencies, up to their values approximately equal to the natural linewidth. On the other hand, the A-T effect starts to dominate at the Rabi frequencies higher than these values [8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
“…A broad absorption minimum (a transparency window) is observed in the theoretical spectrum approximately at Δ p = 63 MHz. In connection with relatively high coupling Rabi frequency ( 51  5 tot ), one can expect that the transparency window in this work is mostly due to the A-T splitting and, to somewhat less extent, due to the EIT (see remarks in the Introduction, and references [8][9][10][11]). The very presence and the approximate position of this absorption minimum could be supposed by taking an analogy with a hypothetical three-level Λ scheme, where the state |5> plays a role of the (only) upper state.…”
Section: Comparison Of Numerical Solutions With Experimental Spectramentioning
confidence: 99%